DIGITAL MARKETING TRAINING FOR KARANG TARUNA’S ENTERPRISE PRODUCTS TO INCREASE BUSINESS TURNOVER - Saputra, Edi; Khair, Miftahul; Thabrani, Gesit (International Journal Mathla’ul Anwar of Halal Issues, 2024)
Karang Taruna is a youth organization which is a partner for community service from universities. Business actors can take advantage of the rapid development of information technology to increase their business volume. Digital marketing, which is now widely used, is not well known by the Karang Taruna in the city of Padang. Karang Taruna youth are also Small Medium Enterprise (SME) actors. Therefore, training in marketing strategy, packaging design, and appropriate media design is needed to reach the target market so that sales volume can increase. The training held contained the Urgency of Utilizing Digital Marketing for SME Products; Powerpoint Based Digital Packaging Design; Digital marketing through social media and marketplace; SME Product Marketing, Halal certification. The results of this activity increasing the knowledge of participants in utilizing online media as a means of product marketing. This provides an opportunity to expand the product market which can have an impact on increasing business turnover.